Improving Machine Efficiency at PT PID Ongkowidjojo: OEE and FMEA Analysis Leading to Significant Gains in Primary Stage 3 - Prameswari, Maria Immaculata; Noya, Sunday; Purnomo, Purnomo (Jurnal Sains dan Aplikasi Keilmuan Teknik Industri (SAKTI), 2024)
This study aims to enhance equipment effectiveness in the primary cigarette manufacturing process at PT. PID Ongkowidjojo, focusing on Stage 3, a critical production phase with significant downtime due to equipment failures. Using Overall Equipment Effectiveness (OEE) and Failure Mode and Effects Analysis (FMEA), the research identified nine key failure modes affecting interconnected machines. Based on these findings, targeted improvements were implemented, including scheduled maintenance, real-time monitoring, periodic cleaning, and spare parts inventory management. As a result, the OEE value increased from 50.52% to 56.57%, driven by improvements in Availability (71.07% to 79.22%) and Quality Rate (92% to 93.36%), despite a slight decline in Performance Rate (77.20% to 76.25%). This study highlights the importance of integrating OEE and FMEA methodologies to reduce downtime and address equipment inefficiencies. By tackling the Six Big Losses, particularly equipment failures, this approach offers actionable insights for maintaining operational efficiency and fostering continuous improvement in manufacturing systems.